1975
DOI: 10.1084/jem.141.1.206
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface immunoglobulin. XI. The appearance of an IgD-like molecule on murine lymphoid cells during ontogeny.

Abstract: An Ig molecule containing L chains and H chains similar to human delta-chains has been detected on the surface of radioiodinated murine lymphoid cells. Newborn mice have only IgM on their splenocytes. Between 10 and 15 days, the IgD-like molecule appears and increases in amount until 3 mo of age, when it is the predominant cell surface Ig in terms of radioactivity. IgD is found only in peripheral lymphoid tissues and is present in larger amounts on peripheral lymph node cells (approximately 85% of surface Ig) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(53 citation statements)
references
References 21 publications
5
48
0
Order By: Relevance
“…1). 5 chains increase from nondetectable levels to approximately 20% of total cell surface immunoglobulin between day 2 and day 12 of age (16,19), while the normal adult ratio of IgD to IgM is as high as 2:1. On the other hand, the density of cell surface IgM per cell does not change significantly during this period (16), although the percent of IgM-bearing cells in the spleen does increase rapidly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 5 chains increase from nondetectable levels to approximately 20% of total cell surface immunoglobulin between day 2 and day 12 of age (16,19), while the normal adult ratio of IgD to IgM is as high as 2:1. On the other hand, the density of cell surface IgM per cell does not change significantly during this period (16), although the percent of IgM-bearing cells in the spleen does increase rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoglobulin M (IgM) is the first and only isotype to be expressed on immature B lymphocytes, while IgD is gradually acquired during the first weeks of life (16,19,27). In the mouse, surface IgD does not approximate adult levels until 3 weeks after birth (27).…”
mentioning
confidence: 99%
“…Only activity against h-chains could be detected by Ouchterlony analysis, and after conjugation to fluorescein, by immunoflurescence staining of fixed cell preparations of various mouse myelomas . Moreover, these antibodies did not precipitate 8-like chains (1,37) from solubilized spleen cells which had been radiolabeled by lactoperoxidasecatalyzed iodination (E . Vitetta, personal communication) .…”
Section: Methodsmentioning
confidence: 99%
“…Scher et al previously demonstrated that Ig + cells which bear a low-to- (9,16). To examine the ratio of surface IgM to IgD on those B lymphocytes of F~ females which were not susceptible to lysis by the absorbed antiserum, we treated F~ female spleen cells with the absorbed antiserum and C. Live cells were recovered by Ficoll-Hypaque centrifugation, labeled with '25I using the lactoperoxidase technique, solubilized with 0.5% NP-40 in phosphate-buffered saline, and the surface Ig precipitated as noted in the Materials and Methods section.…”
Section: Analysis Of Cellmentioning
confidence: 99%